2018
DOI: 10.1101/286302
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-specific changes in the aphid DNA methylation landscape

Abstract: Aphids present an ideal system to study epigenetics as they can produce diverse, but genetically identical, morphs in response to environmental stimuli. Here, using whole genome bisulphite sequencing and transcriptome sequencing of the green peach aphid (Myzus persicae), we present the first detailed analysis of cytosine methylation in an aphid and investigate differences in the methylation and transcriptional landscapes of male and asexual female morphs. We find that methylation primarily occurs in a CG dinuc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(50 citation statements)
references
References 62 publications
8
42
0
Order By: Relevance
“…Out of a total of 1,029 morph-biased genes, 539 (52.4%) are specifically upregulated in males relative to the common wingless asexual female morph (Figure 6b). These male-biased genes are significantly enriched on the M. persicae X chromosome (binomial test: p = 2.38x10 -6 ; Figure 6c), confirming our previous results obtained using a fragmented genome assembly (Mathers et al 2019) and matching patterns of male-biased gene expression observed in A. pisum (Jaquiéry et al 2013;Purandare et al 2014;Pal and Vicoso 2015). Using gene expression data for asexual females, we confirm that the X chromosome has significantly lower gene expression than the autosomes (Wilcoxon rank-sum test: W = 715,820, p < 2.2x10 -16 ; Figure 6d) and that this is particularly pronounced for the 5' and 3' ends of the chromosome (Figure 6e).…”
Section: Patterns Of Gene Expression Along the M Persicae Genomesupporting
confidence: 89%
See 2 more Smart Citations
“…Out of a total of 1,029 morph-biased genes, 539 (52.4%) are specifically upregulated in males relative to the common wingless asexual female morph (Figure 6b). These male-biased genes are significantly enriched on the M. persicae X chromosome (binomial test: p = 2.38x10 -6 ; Figure 6c), confirming our previous results obtained using a fragmented genome assembly (Mathers et al 2019) and matching patterns of male-biased gene expression observed in A. pisum (Jaquiéry et al 2013;Purandare et al 2014;Pal and Vicoso 2015). Using gene expression data for asexual females, we confirm that the X chromosome has significantly lower gene expression than the autosomes (Wilcoxon rank-sum test: W = 715,820, p < 2.2x10 -16 ; Figure 6d) and that this is particularly pronounced for the 5' and 3' ends of the chromosome (Figure 6e).…”
Section: Patterns Of Gene Expression Along the M Persicae Genomesupporting
confidence: 89%
“…Indeed, our gene counts are much closer to the independent annotations of A. pisum LSR1 v2 and M. persicae clone G006 v2 carried out by Thorpe et al (2018), who used the same annotation pipeline employed in this study (BRAKER [Hoff et al 2015[Hoff et al , 2019) and found 27,676 and 25,726 genes in A. pisum and M. persicae, respectively. Additionally, in the case of M. persicae, the use of additional RNA-seq data from diverse morphs sequenced for this study and elsewhere (Mathers et al 2019) may have contributed to the discovery of additional genes. Finally, our improved genome assemblies may also contribute to the observed differences in gene count.…”
Section: Chromosome-scale Assemblies Of the M Persicae And A Pisum mentioning
confidence: 95%
See 1 more Smart Citation
“…As such, the analysis described here reflects on both abiotic differences between estuaries over the 10‐year daily mean differences between sites and the 10‐day daily mean differences prior to sampling (Figure c). Significantly differentially methylated regions (DMRs) were identified for all comparisons using a minimum percent methylation difference between populations of 15% and a Benjamini‐Hochberg adjusted p ‐value ( q ‐value) less than or equal to .05 (Mathers et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, while A. pisum may be an important sap-feeding pest model, very little is known about its nymphal development compared to insect models that belong to other insect orders. Previous developmental studies in A. pisum have primarily focused on polyphenisms observed in the adult life stages; male vs. female, alate vs. apterous morphs, and sexual vs. asexual reproduction [4,5,6,7,8,9,10,11,12,13,14,15,16]. While understanding the development of these polyphenisms is extremely important in aphids, having a deeper understanding of nymphal development is also important because while these phenotypes are visible in adult life stages, patterning and fate specification occur during embryonic and nymphal life stages.…”
Section: Introductionmentioning
confidence: 99%